2020
DOI: 10.3390/ijerph17238800
|View full text |Cite
|
Sign up to set email alerts
|

Mediation Effect of Perceived Fitness on the Relationship between Self-Efficacy and Sport Practice in Spanish Adolescents

Abstract: There has been a decrease in sports practices among the adolescent population, and several authors have tried to identify variables that can explain this decrease by analyzing psychosocial aspects such as perceived fitness and self-efficacy. Therefore, the purpose of this research is to examine the association of perceived fitness and self-efficacy with sport practices and to determine whether perceived fitness is a mediator of the association between self-efficacy and sport practice in Spanish adolescents. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
2
5
0
1
Order By: Relevance
“…Since the evaluation of self-efficacy involves the judgment of one's own ability to organize and perform certain tasks [40], it was logical that facets of sport participation would be positively associated with PL. These considerations are supported by previous studies showing that sports participation is positively related to self-efficacy among 13-to 17-year-old students [41].…”
Section: Validitysupporting
confidence: 84%
“…Since the evaluation of self-efficacy involves the judgment of one's own ability to organize and perform certain tasks [40], it was logical that facets of sport participation would be positively associated with PL. These considerations are supported by previous studies showing that sports participation is positively related to self-efficacy among 13-to 17-year-old students [41].…”
Section: Validitysupporting
confidence: 84%
“…On the other hand, physical self-concept is a mental representation concerning personal physical characteristics [23,24]. It has been observed that both self-perceptions have a great impact on the initiation or cessation of behaviors in contexts of physical practice, as well as on the motivation which is generated towards this type of behavior [25,26]. In this sense, Fraile-García et al [27] highlighted positive relationships between motor self-efficacy and enjoyment in PE classes in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…The young athletes' confidence in their ability to successfully accomplish a particular sport is a key mediator in predicting sources of sport satisfaction (Arribas-Galarraga et al, 2020), and it should be considered developmentally over the course of continuous sport practice. This reinforces the importance of providing young athletes with opportunities that can foster recognition of their ability to achieve a goal or succeed in different tasks (Teques et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Youth participation in sports has been significantly and positively associated with perceived self-efficacy (Arribas-Galarraga et al, 2020; Brusokas & Malinauskas, 2014; Coalter & Taylor, 2010; Reverdito, Carvalho, et al, 2017; Teques et al, 2019). Teques et al (2019) investigated parental involvement in sports and psychological variables of young athletes (aged 14–18 years) at different performance levels.…”
Section: Introductionmentioning
confidence: 99%